Investigation of microstructural damage in air-entrained recycled concrete under a freeze–thaw environment. (25th January 2021) - Deng, Xianghui; Gao, Xiaoyue; Wang, Rui; Gao, Mingxian; Yan, Xiaoxia; Cao, Weiping; Liu, Jintao
Highlights: Investigating the pore distribution of RAC and ARAC during freeze–thaw cycles. Revealing the relationship between flexural strength and pore distribution of recycled concretes. Establishing the relationship between the crack proportion of ARAC and freeze–thaw cycles. Abstract: Recycled aggregate concrete (RAC) is a type of multiphase porous material. Its aggregate, admixture, and environment have a crucial impact on its pore structure. Nuclear magnetic resonance (NMR), a nondestructive testing method, was adopted to demonstrate the process of air-entrained recycled coarse aggregate concrete (ARAC) and non-ARAC microstructural damage in a freeze–thaw environment. NMR outcomes showed that the addition of recycled coarse aggregate (RCA) has a certain effect on the distribution of different pores and porous quality of the concrete. Pore structure of recycled concrete with a replacement rate of 25% and 50% was similar. Proportion of macropores and cracks increases significantly when the replacement rate is greater than 75%. The proportion of mesopores (radius of 0.01–0.05 μm) and macropores (radius of 0.05–1 μm) in concrete increased by 13.31%–21.44% and frost resistance of concrete improved with the incorporation of air-entraining admixture (AEA). Proportions of macropores and cracks (radii larger than 1 μm) in the concrete increased while the proportion of micropores (radii less than 0.01 μm) and mesopores decreased and T2 spectral area of concrete gradually increased and moved to the right with increasing freeze–thaw cycles. Moreover, the change of crack proportion of ARAC with freeze–thaw cycles is in accordance with the distribution law of second–order polynomial. Notably, changes in the above microstructure were reflected in macroscopic flexural strength. The flexural strength of recycled concrete was remarkably affected by the total proportion of mesopores and macropores. The flexural strength of recycled concrete was high when the total proportion of mesopores and macropores was between 55% and 74%. The decrease in flexural strength of recycled concrete with increasing freeze–thaw cycles was consistent with the change of crack proportion.